Calcium Carbonate from Clam Shell as a Thermal Conductor in Particulate Filled Polymer Matrix Composites - Yusof, Mahshuri; Muhammad Afifi, Amalina; Tahirah Razali, Nur; Sawawi, Marini; Razak Abdul Karim, Abdul (International Journal of Engineering and Technology, 2018)
The thermal conductivity of the raw and stearic acid treated calcium carbonate (CaCO3) from clam (Polymesoda bengalensis) shell powder infused in unsaturated polyester matrix has been measured. Â Eight different mean diameter sizes of clam shell filler were infused into unsaturated polyester (UPE) matrix. Thermal conductivity of neat UPE sample and when embedded with raw and stearic acid treated CaCO3 filler with different mean diameter sizes and filler loadings were measured according to ASTM E1225-99. The result showed that UPE matrix composites with untreated clam shell produced higher thermal conductivity than treated clam shell. At constant filler content, the thermal conductivity of UPE/CaCO3 composites was increased gradually as the filler size was decreased. The higher the filler content, the higher the thermal conductivity of the composites. Therefore, the inclusion of higher filler loading with finer filler size of seafood waste from clam shell can improve the performance of polymer matrix composites as a heat conductor.Â Â Â